Teknologi produksi non-pertanian sebagai motor penggerak pembangunan perdesaan: Sebuah studi pustaka - Awan Setya Dewanta (Economic Journal of Emerging Markets, 1997)
Economic development centered in the urban areas has increased migration from rural areas to urban areas dramatically. As a consequence, labor force and farmland became scarce. Although this circumstance has risen productivity of the farmer, the fact is that the prosperity of the farmer is still not fulfilled sustainable yet. It is evoked by the price inelasticity of the crops. Therefore, wehave to develop non-agricultural and non-rural technologies. Some research in several countries based on both the evolutionary development theory and Haymer and Resnick's development models (1969) that has been developed, at least showed that indeed the change of non-agricultural production technology could increased prosperity rather than agricultural production technology. It means that the change ofnon agricultural technology can be used as an activator motor in agricultural development. The realization of it will at once return rural areas as an economic areas again.